Usefulness of cholangioscopic-guided mapping biopsy using SpyGlass DS for preoperative evaluation of extrahepatic cholangiocarcinoma: a pilot study - Ogawa, Takahisa; Ito, Kei; Koshita, Shinsuke; Kanno, Yoshihide; Masu, Kaori; Kusunose, Hiroaki; Sakai, Toshitaka; Murabayashi, Toji; Hasegawa, Sho; Noda, Yutaka (Endoscopy International Open, 2018)
Background and study aims Evaluation of longitudinal tumor extent is indispensable for curative surgical treatment of extrahepatic cholangiocarcinoma. The aim of this study was to evaluate the usefulness and feasibility of cholangioscopic-guided mapping biopsy using a newly developed peroral digital cholangioscope, SpyGlass DS (SpyDS), for preoperative evaluation of extrahepatic cholangiocarcinoma.Patients and methods Thirteen patients (mean age, 75 years; male 10, female 3) with extrahepatic cholangiocarcinoma who underwent cholangioscopic-guided mapping biopsy using SpyDS for preoperative evaluation were included in this study. Successful cholangioscopic-guided mapping biopsy was defined as the acquisition of specimens sufficient for histopathological diagnosis.Results The mean number of biopsies was 5 per patient. The overall success rate for cholangioscopic-guided mapping biopsy was 88 % (59/67). The success rate for cholangioscopic-guided mapping biopsy from the confluence of the right and left hepatic ducts was 89 %, that from the B4 confluence was 93 %, that from the confluence of the right anterior and right posterior segmental ducts was 86 %, that from the intrapancreatic common bile duct was 67 %, and that from the main lesion was 100 %. The overall diagnostic accuracy of longitudinal tumor extent at the hepatic side, the duodenal side and overall by cholangioscopic findings and mapping biopsy, was 88 % (7/8), 88 % (7/8) and 88 % (7/8), respectively. Assessment according to location of the main lesion revealed that diagnostic accuracy in the patients with distal bile duct carcinoma was 100 % (5/5) and that in patients with perihilar bile duct carcinoma was 66 % (2/3). Complications after the procedure did not occur in any patients.Conclusions Cholangioscopic-guided mapping biopsy using SpyDS is thought to be feasible for preoperative evaluation of extrahepatic cholangiocarcinoma.